Traumatic encephalopathy syndrome: application of new criteria to a cohort exposed to repetitive head impacts - Ritter, A.; Shan, G.; Montes, A.; Randall, R.; Bernick, C. (British Journal of Sports Medicine, 2023)
Objective: To examine the characteristics of those who fulfil the recent National Institute of Neurological Disease and Stroke (NINDS) Consensus Diagnostic Criteria for Traumatic Encephalopathy Syndrome (TES) and test whether they show differences in MRI-based regional brain volumes, cognitive domains, and certain plasma biomarkers.